The use of tensiomyography in older adults: a systematic review - Pus, Katarina; Paravlic, Armin H.; Šimunič, Boštjan (Frontiers in Physiology, 2023)
Introduction: Ageing of skeletal muscles results in a cascade of events negatively affecting muscle mass, strength, and function, leading to reduced mobility, increased risk of falls, disability, and loss of independence. To date, different methods are used to assess muscle mechanical function, Tensiomyography (TMG) being one of them. The aim of this review was twofold: to summarise the evidence-based usefulness of the TMG in older adults and to establish reference values for the main TMG parameters in older adults. Methods: The PubMed, Web of Science, SportDiscus and TMG databases were searched from inception until 25th of December 2022. Studies investigating older adults (aged 60 + years) that reported TMG-derived parameters such as contraction time (Tc) and/or maximal displacement (Dm) were included. Methodological quality was assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: In total, eight studies satisfied the inclusion criteria. TMG has been used on different groups of older adults including asymptomatic, master athletes, patients with peripheral arterial disease and patients with end-stage knee osteoarthritis with mean age 71.5 ± 5.38 (55.7 % males). The most evaluated were leg muscles such as vastus lateralis (VL), gastrocnemius medialis (GM), and biceps femoris (BF). The present review demonstrates that TMG is used to assess neuromuscular function in asymptomatic and diseased older adults. When compared to asymptomatic, power master athletes, knee osteoarthritis patients and patients diagnosed with peripheral arterial disease have the shortest Tc in BF, VL and GM muscles, respectively. On the other hand, endurance master athletes showed the longest Tc in all three evaluated muscles. Less mobile, nursing-home residents, showed higher Dm in VL and BF while lower Dm in GM than asymptomatic group. The knee osteoarthritis group showed the largest Dm in BF and VL, while having the smallest Dm in GM. Conclusions: TMG can serve as a valuable tool for assessing neuromuscular function in older adults. The method is sensitive to muscle composition, architecture and (pre) atrophic changes of skeletal muscles and might be responsive to muscle quality changes in ageing and diseased populations.